Patient response and remission in respiratory disease: Special focus on severe asthma and chronic obstructive pulmonary disease - Stefania Colantuono; Francesco Menzella; Pier-Valerio Mari; Francesco Macagno; Francesco Lombardi; Ilaria Baglivo; Cristiano Caruso (Journal of International Medical Research)
Over the past decades, monoclonal antibodies have been playing a pivotal role in the treatment of chronic inflammatory airway diseases. Currently, ample data are available on the efficacy and safety of biologics in asthma from randomized controlled trials and open-label trials; conversely, limited data are available on the use of biologics in chronic obstructive pulmonary disease. In this context, once the fundamental role of inhaled corticosteroid/long-acting β2-agonist/long-acting muscarinic antagonist therapy is established, clinical response and disease remission, based on clinical and functional response parameters such as oral corticosteroid need, annual exacerbation rates, and lung function, are the key factors driving the clinical and therapeutic management. This narrative review has summarized the literature data from randomized controlled trials and real-life experience on currently available biologics in asthma and chronic obstructive pulmonary disease. The role of inhaled corticosteroid, long-acting β2-agonist, and long-acting muscarinic antagonist therapy has been further investigated with a particular focus on drug-free concept.